2021
DOI: 10.1111/ppl.13589
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous melatonin mitigates salinity‐induced damage in olive seedlings by modulating ion homeostasis, antioxidant defense, and phytohormone balance

Abstract: Melatonin (MEL) is a ubiquitous molecule with pleiotropic roles in plant adaption to stress. In this study, we investigated the effects of foliar spray of 100 and 200 μM MEL on the biochemical and physiological traits linked with the growth performance of olive seedlings exposed to moderate (45 mM NaCl) and severe (90 mM NaCl) salinity. Both salt stress conditions caused a considerable reduction in leaf relative water content and the contents of photosynthetic pigments (carotenoids, chlorophylls a and b, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 81 publications
2
19
0
Order By: Relevance
“…Conversely, our results showed that salt stress showed a greater increment in ACC, IPA, IAA and ABA in leaves of Chaoyouqianhao, whereas only the increased ABA content was observed in Huanghuazhan. Similar results were obtained by Zahedi et al, who reported that IAA and ABA contents increased in the presence of salinity in olive seedlings 75 .…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, our results showed that salt stress showed a greater increment in ACC, IPA, IAA and ABA in leaves of Chaoyouqianhao, whereas only the increased ABA content was observed in Huanghuazhan. Similar results were obtained by Zahedi et al, who reported that IAA and ABA contents increased in the presence of salinity in olive seedlings 75 .…”
Section: Discussionsupporting
confidence: 91%
“…Salinity stress is one of the serious threats to crop growth and development. Many studies indicate that melatonin enhances tolerance to salinity stress in various plant species, including Arabidopsis , Brassica napus , rice, wheat, tomato, cucumber, Malus domestica , Limonium bicolor , sunflower, and olive [ 12 , 35 , 36 , 40 , 42 , 47 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. Within these studies, melatonin regulated ion homeostasis, especially Na + and K + homeostasis, thus alleviating the salinity damage.…”
Section: Melatonin Acts As An Antioxidant To Establish Redox Homeosta...mentioning
confidence: 99%
“…Seedling treatment with inorganic and organic agents greatly reduces the detrimental effects of stress and enhances essential nutrient content ( Qiu et al, 2014 ; Cantabella et al, 2017 ; Ghassemi-Golezani and Farhangi-Abriz, 2018 ; Silva et al, 2020 ; Zahedi et al, 2021 ). In our present work, the pretreatment of seedlings with H 2 O 2 increased the fresh and dry weights of salinity-treated seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on different plants have given controversial conclusions ( Qiu et al, 2014 ; Song et al, 2021 ), which means the roles of JA in plant salt stress tolerance are sophisticated. In this process, the combined action of JA with other plant hormones, such as ABA, ethylene, auxin, and salicylic acid, plus the regulation of hormonal homeostasis may jointly contribute to plant growth under salt stress ( Raza et al, 2021 ; Zahedi et al, 2021 ; Zhao et al, 2021 ; Zhu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%